Exploring the Everyday Lived Experience of African American People Living with HIV/AIDS (PLWH) in the Rural South - Jill E. Rowe (HIV/AIDS Research and Treatment-Open Journal, 2019)
Aims/Objectives Despite previous findings attesting to the syndemic nature of human immunodeficiency virus (HIV), chronic disease and mental illness coordination of these issues remains a significant barrier to initiating and maintaining the delivery of mental and physical health care to persons living with HIV (PLWH). These inequities are even greater when applied to rural settings, particularly in areas that are medically underserved. To date, there is scarce research regarding the lived experiences of African American PLWH in rural settings. Constructivist grounded theory was used to analyze this qualitative data set. These discourses provide a rich narrative regarding effective systems of care, the context in which these processes take place and related constraints or limitations of the current systems. Methods In-depth interviews with 24 African American PLWH both inside (N=20) and outside (N=4) of care in rural Northwestern Virginia were conducted. Rural African American PLWH were queried about their perceptions of the provision of HIV health care services, barriers to linkages to care, retention of PLWH in care, and recommendations for improving HIV health care services for rural PLWH. Results Participants offered insights on the linkages to health and mental health care consistent with the pattern recommended by the cascade of care (i.e. pre-screening, testing, refer to treatment, treatment and sustain treatment). Participants identified contextual factors, including traumatic events, medication (side effects), other chronic health issues, issues with the current health and mental health system, stigma, and lack of social support. We highlight PLWH’s recommendations for linking rural PLWH into care and sustaining that care. Conclusion We discuss the implications of these findings for programmatic development in the rural context.